Inflammation markers and the risk of hypertension in people living with HIV - Ou-Yang, Hui; Fu, Hai-Yan; Luo, Yu; Xu, Zhao-Yuan; Liu, Jun; Gao, Rui; Duan, Jin-Yu; Mao, Ya-Chao; Li, Hong-Juan; Du, Ying-Rong (Frontiers in Immunology, 2023)
Background: The incidence of hypertension is high in people living with HIV (PLWH). High-sensitivity C-reactive protein (hsCRP), systemic inflammation response index (SIRI), and neutrophil-to-monocyte ratio (NMR) are considered economic and convenient parameters that reflect the levels of inflammation in patients. Our aim was to explore whether indirect inflammation markers are associated with hypertension in PLWH. Methods: This was a case-control study. The case group (hypertension) comprised PLWH with hypertension, and the control group (non-hypertension) comprised sex- and age-(± 3 years)-matched PLWH without hypertension. Demographic parameters, hsCRP, neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), systemic immune- inflammation index (SII), SIRI, lymphocyte-to-monocyte ratio (LMR), platelet-to-neutrophil ratio (PNR), platelet-to-monocyte ratio (PMR), NMR, time to HIV diagnosis, antiretroviral therapy (ART) duration, recent CD4+ and CD8+ cell counts, recent CD4+/CD8+ ratio, recent HIV viral load (HIV-RNA) ,and recent ART regimen were obtained from the patients’ electronic medical records. A t-test or Wilcoxon rank-sum test was performed to compare differences between the two groups, and conditional logistic regression was used to analyze the risk factors of hypertension. Correlations between inflammation markers and CD4+ cell counts, CD8+ cell counts, and CD4+/CD8+ ratio were analyzed using Spearman’s correlation. Results: In the hypertension group, body mass index (BMI), hsCRP, NLR, SII, SIRI, NMR, time to HIV diagnosis, ART duration, CD4+ and CD8+ cell counts, and CD4+/CD8+ ratio, the ratio of HIV-RNA < 100 copies/mL were all higher than those in the non-hypertension group, while the PNR was lower than those in the non-hypertension group. ART duration, CD4+ cell counts, HIV-RNA < 100 copies/mL, hsCRP, SIRI, and NMR were positively associated with hypertensive risk in PLWH. CD8+ cell counts and CD4+/CD8+ ratio were negatively associated with hypertensive risk in PLWH. SIRI was negatively correlated with CD4+ cell counts, CD8+ cell counts, and CD4+/CD8+ ratio. Conclusions: We identified positive associations between inflammation markers hsCRP, SIRI, NMR and hypertensive risk in PLWH. Alleviating inflammation may help control or delay the occurrence of hypertension in PLWH.